Rugged Regulatory Landscapes - Singapore Management University (Institutional Knowledge at Singapore Management University, 2013)
Indonesia’s miners are adept at scaling the country’s rugged regulatory landscape. But their legendary resilience may be put to the test in 2014. Written by Dharma Djojonegoro, President Director of Indonesian mining services provider PT Multi Nitrotama Kimia (MNK).